Dietary prebiotics and probiotics influence growth performance, nutrient digestibility and the expression of immune regulatory genes in snakehead (Channa striata) fingerlings - Munir M.B.; Hashim R.; Chai Y.H.; Marsh T.L.; Nor S.A.M. (Elsevier B.V., 2024)
Indexed by WOS/ Scopus